Anis Nagy’s Novel, In the Context of Existentialism - Saeed, Aziza; Tabassum, Khizra; Manzoor, Sobia (sourcecoder, 2024)
Anis Nagy is one of the writers influenced by the existential movement. He made migration, collapse, social unrest, hypocrisy and existential crisis the subject of his novels. His existential novels are a lament of the individual’s defeat and inner closeness. Since Anis Nagi’s own life was one of deprivation and discomfort, most of his characters can be described as a part of his own being, which is neither related to society. Can establish a relationship Nor can they maintain the identity of their existence.